Symbolic Meaning and Function Jaka Poleng's Following Story and Burok Art - Ilman Elfikri, Zidnie; Nuryatin, Agus; Doyin, Mukh (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Folklore is a story born from fictional ideas and true stories. Folklore of each region generally tells about the past from one generation to the next. The folklore of Jaka Poleng and the Arts of Burok is a form of folklore from the Brebes area which is told in the form of true stories and passed down from generation to generation through oral and written traditions. Every folklore must have symbols and meanings that describe certain social characteristics. This study aims to examine the symbolic meaning and function of the Jaka Poleng folklore and Burok Arts for the people of Brebes Regency. This research uses Paul Ricoeur's hermeneutical point of view and William R. Bascom's theory of functions. The study of symbolic meaning from a hermeneutic point of view is a textual interpretation of the meaning of the readings contained in the stories of Jaka Poleng and Seni Burok. The implementation of the symbolic meaning contained in the story is divided into three meanings, namely; respect, resistance, and religion. The functions of the two folklores are a) fantasy function, b) as a means of validation, c) as a means of education, d) as a means of social control of society, and e) as cultural validation.